Combined in-situ attenuated total reflection-Fourier transform infrared spectroscopy and single molecule force studies of poly(acrylic acid) at electrolyte/oxide interfaces at acidic pH - Neßlinger, Vanessa; Orive, Alejandro G.; Meinderink, Dennis; Grundmeier, Guido (Journal of Colloid and Interface Science)
Keywords: Colloid and Surface Chemistry; Surfaces; Coatings and Films; Biomaterials; Electronic; Optical and Magnetic Materials

Ultrahigh water sorption on highly nitrogen doped carbonaceous materials derived from uric acid - Kossmann, Janina; Rothe, Regina; Heil, Tobias; Antonietti, Markus; Lopez Salas, Nieves (Journal of Colloid and Interface Science)
Keywords: Colloid and Surface Chemistry; Surfaces; Coatings and Films; Biomaterials; Electronic; Optical and Magnetic Materials

Lifshitz analysis of dispersion forces based on quantitative reflection electron energy loss spectroscopy - Wiesing, M.; Grundmeier, Guido (Journal of Colloid and Interface Science)

Embedding DNA in surfactant mesophases: The phase diagram of the ternary system dodecyltrimethylammonium–DNA/monoolein/water in comparison to the DNA-free analogue - Bilalov, Azat; Elsing, Jonas; Haas, Eva; Schmidt, Claudia; Olsson, Ulf (Journal of Colloid and Interface Science)
Keywords: Colloid and Surface Chemistry; Surfaces; Coatings and Films; Biomaterials; Electronic; Optical and Magnetic Materials

Effect of shear on vesicle and lamellar phases of DDAB/lecithin ternary systems - Youssry, Mohamed; Coppola, Luigi; Nicotera, Isabella; Ar, Gönül; Schmidt, Claudia (Journal of Colloid and Interface Science)
Keywords: Colloid and Surface Chemistry; Surfaces; Coatings and Films; Biomaterials; Electronic; Optical and Magnetic Materials

Microemulsion approach to neodymium, europium, and ytterbium oxide/hydroxide colloids—Effects of precursors and preparation parameters on particle size and crystallinity - Rill, Christoph; Bauer, Matthias; Bertagnolli, Helmut; Kickelbick, Guido (Journal of Colloid and Interface Science)
Keywords: Colloid and Surface Chemistry; Surfaces; Coatings and Films; Biomaterials; Electronic; Optical and Magnetic Materials

Simulation of the hydrodynamic drag of aggregated particles - Binder, Christian; Feichtinger, Christian; Schmid, Hans-Joachim; Thürey, Nils; Peukert, Wolfgang; Rüde, Ulrich (Journal of Colloid and Interface Science)
The drag force on aggregates and partially sintered agglomerates is assessed using the lattice Boltzmann method (LBM) and accelerated Stokesian dynamics (ASD). Both methods have been compared in terms of accuracy and computational effort. It is shown that they give comparable results if all numerical parameters are controlled carefully. LBM requires a much higher computational effort, however, in contrast to ASD it is able to simulate partially sintered agglomerates as well. The results show that even a very small amount of sintering leads to a significant reduction in the drag force. The analysis of the drag force on agglomerates as well as on aggregates shows that there is no simple geometric quantity which is uniquely related to the drag force. Moreover, there is a significant variation in drag force for single aggregates at different orientations or for the orientation averaged drag force of different aggregates of the same size. This is explained by the structural effects which may lead to a variation in the drag force up to +-20%.

Coexisting lamellar phases in water–oil–surfactant systems induced by the addition of an amphiphilic block copolymer - Frank, Christian; Strey, Reinhard; Schmidt, Claudia; Stubenrauch, Cosima (Journal of Colloid and Interface Science)
Keywords: Colloid and Surface Chemistry; Surfaces; Coatings and Films; Biomaterials; Electronic; Optical and Magnetic Materials

Colloid–polymer mixtures in solution with refractive index matched acrylate colloids - Kramer, Thomas; Scholz, Stephanie; Maskos, Michael; Huber, Klaus (Journal of Colloid and Interface Science)
Keywords: Colloid and Surface Chemistry; Surfaces; Coatings and Films; Biomaterials; Electronic; Optical and Magnetic Materials

A Doubly Branched Nonionic Oligooxyethylene V-Amphiphile: Effect of Molecular Geometry on Liquid-Crystalline Phase Behavior, 3 - Kratzat, Krystyna; Schmidt, Claudia; Finkelmann, Heino (Journal of Colloid and Interface Science)
Keywords: Colloid and Surface Chemistry; Surfaces; Coatings and Films; Biomaterials; Electronic; Optical and Magnetic Materials

Characterization of Worm-like Micelles Containing Solubilized Dye-Molecules by Light Scattering Techniques - Herzog, Bernd; Huber, Klaus; Rennie, Adrian R. (Journal of Colloid and Interface Science)
Keywords: Colloid and Surface Chemistry; Surfaces; Coatings and Films; Biomaterials; Electronic; Optical and Magnetic Materials

Mixtures of Polyacrylic Acid and Nonionic Surfactants at the Water/Air Interface - Maloney, Colette; Huber, Klaus (Journal of Colloid and Interface Science)
Keywords: Colloid and Surface Chemistry; Surfaces; Coatings and Films; Biomaterials; Electronic; Optical and Magnetic Materials

Interactions in mixed interfaces of binary surfactant solutions - Huber, Klaus (Journal of Colloid and Interface Science)
Keywords: Colloid and Surface Chemistry; Surfaces; Coatings and Films; Biomaterials; Electronic; Optical and Magnetic Materials